Study of relationship of vascular pedicle width with cardiothoracic ratio and hemodynamic data in ventilated icu patients - Azura Sharena, Yahaya (2009)
The relationship of vascular pedicle width with cardiothoracic ratio, weight and CVP in ventilated ICU patients. Intravascular volume assessment is one of the main concern in managing critically ill ventilated patients. Invasive hemodynamic monitoring is commonly used to assess the intravascular volume status. Due to its invasiveness and other related serious complications such as bacteremia, endocarditis and thrombogenesis, the non-invasive diagnostic testing has gained increase importance. Chest radiograph is the readily available and commonest tool used in managing critically ill ventilated patients. It is one of invasive method to determine the intravascular volume status. However, due to subjectivity on interpreting chest radiograph, an objective measurement like VPW is used to assess intravascular volume. To determine the relationship of vascular pedicle width with hemodynamic data (weight and CVP) and CTR in ventilated patient using supine portable chest radiograph A cross sectional study was done from May 2006 ~til December 2006 involving 140 adult ventilated patients in ICU and Neuroscience ICU of Hospital University Sains Malaysia. The hemodynamic data (weight and CVP) was read within 1 hour after the chest radiograph performed. Computed chest radiography is used for evaluation of the VPW. The VPW and CTR were measured by researcher in separated occasion without clinical data related to patients available One hundred and forty adult ventilated patients were included in this study. Out of 140 subjects, 73 were male and 67 patients were female. One hundred twenty two out of 140 patients were Malays (87%) whereas 18 (13%) were Chinese. The mean age was 46.6 years old and the mean weight was 62.6 kg. The mean value for VPW was 64.3 mm and the mean value for CTR and CVP was 0.5 and 13.0 mmHg respectively. There was significant relationship between weight with VPW (p<O.OO 1 ), CVP with VPW (p<O.OO 1) and CTR with VPW (p<0.001). However, using the multiple linear regression analysis, it is found that only CTR has a significant relationship with VPW as compare to weight and CVP. The VPW was found to be the only association seen with pulmonary edema among study population (p<O.OO 1) by using the multiple logistic regression analysis. When there is increased of VPW measurement by 0.17 mm, the patients will have 1.2 time risk of having pulmonary edema (p<O.OO 1 ) There was statically significant correlation seen between the weight, CVP and CTR with the VPW. The most significant correlation was seen between CTR with VPW. The VPW was the only associated seen with pulmonary edema. When there is increased of VPW measurement by 0.17 mm, the patients will have 1.2 time risk of having pulmonary edema. The mean value ofVPW was noted to be smaller as compared to other previous study. This suggest that the cut off VPW measurement used to differentiated between high to low or normal intravascular volume could be smaller in our population body habitus.